Blake in the Nineties
XIII, 240 p.
Keywords: The 1990s have witnessed a major reassessment of Blake initiated by a new and more rigorous comprehension of his modes of production, which in turn has led to re-evaluation of other literary and cultural contexts for his work. Blake in the Nineties grapples with the implications of the new bibliography for Blake studies, in its editorial, interpretative, and historical dimensions. As well as providing an international overview of recent Blake criticism, the collection contributes to current debates in a variety of disciplines dealing with the Romantic period, including art history, counter-Enlightenment-scholarship, theology and hermeneutic theory.